2016
DOI: 10.3892/or.2016.4664
|View full text |Cite
|
Sign up to set email alerts
|

Rhapontigenin inhibits TGF-β-mediated epithelial-mesenchymal transition via the PI3K/AKT/mTOR pathway and is not associated with HIF-1α degradation

Abstract: The epithelial-mesenchymal transition (EMT) is a pivotal event in cancer cell invasion and metastasis. Emerging evidence suggests that rhapontigenin (Rha) may impede the progression of cancer by disrupting angiogenesis and the EMT. However, the underlying mechanism of Rha has not yet been clarified. In this study, we used transforming growth factor β (TGF-β) to trigger EMT in diverse types of cancer cells and revealed that Rha inhibited TGF-β-induced EMT and derived‑cell invasiveness. The effects of TGF-β were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…These results suggest that mTOR regulates EMT in HG conditions via the TGF-β1/PI3K/Akt signalling pathway. This is in agreement with a previous study, in which it was demonstrated that PI3K/Akt was activated during TGF-β1-induced EMT in cancer cells (44).…”
Section: Gsh (Mg/g Protein) T-sod (U/mg Protein) Mda (µMol/g Protein)supporting
confidence: 94%
“…These results suggest that mTOR regulates EMT in HG conditions via the TGF-β1/PI3K/Akt signalling pathway. This is in agreement with a previous study, in which it was demonstrated that PI3K/Akt was activated during TGF-β1-induced EMT in cancer cells (44).…”
Section: Gsh (Mg/g Protein) T-sod (U/mg Protein) Mda (µMol/g Protein)supporting
confidence: 94%
“…We have also seen evidence of epithelial-mesenchymal transition (EMT) of amnion epithelial cells under oxidative stress conditions. TGF-β is a major mediator of EMT [ 61 65 ]. Molecular networks in CSE treated exosomes confirms that TGF-β mediated EMT may be functional in AECs under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Another limitation is that HFT differentiation was only analyzed using Oil Red O staining, not differentiation markers or fluorescence-activated cell sorting analysis. Additionally, previous studies have reported other potential molecular pathways that may be associated with the proliferation (33)(34)(35)(36)(37) and differentiation of HFTs, including the Wnt signal transduction pathway, forkhead box P1-mediated oxidative stress and epidermal growth factor receptor/extracellular signal-regulated kinases/AKT, c-Jun N-terminal kinases/c-Jun and TGF-β pathways (38). The present study only investigated the PI3K/AKT signaling pathway in HFTs.…”
Section: Discussionmentioning
confidence: 88%